Sustained Release of MiR-217 Inhibitor by Nanoparticles Facilitates MSC-Mediated Attenuation of Neointimal Hyperplasia After Vascular Injury - Yu, Hong; Hua, Yutao; He, Yecheng; Wang, Yin; Hu, Xingjian; Chen, Si; Liu, Junwei; Yang, Junjie; Li, Huadong (Frontiers in Cardiovascular Medicine, 2021)
Mesenchymal stem cells (MSCs) have a great therapeutic potential for regenerative medicine owing to their intrinsic capability of self-renewal. MSCs have been proven capable of differentiating into endothelial cells (ECs) in vitro, thereby increasing vascular density in a mouse hindlimb ischemia model. However, the therapeutic potential of MSCs is limited, and their mechanism of action is still not fully understood. In this study, we found that intravenously-administered MSCs can protect femoral artery from neointimal hyperplasia in a standard mouse wire injury model. Intravenously administered MSCs localize to the luminal surface of the injured artery within 24h after injection and subsequently differentiate into endothelial cells. In contrast to injected mouse fibroblasts or phosphate buffered saline (PBS) alone, MSCs injected into mice with injured femoral arteries were capable of significantly inhibiting neointimal proliferation and migration of vascular smooth muscle cells. Being an endogenous suppressor of SIRT1, MiR-217 inhibits endothelial differentiation of MSCs and, therefore, is potentially amenable to therapeutic modulation for vascular injury treatment. Transfection of MSCs with Poly Lactic-co-Glycolic Acid (PLGA) nanoparticles encapsulating a miR-217 mimic abolished endothelial differentiation of MSCs at the luminal surface of the injured arteries as well as the therapeutic effect of MSCs. On the contrary, silencing of endogenous miRNA-217 improved the efficacy of MSC treatment and prevented neointimal hyperplasia. Our study thus gave rise to a new strategy of augmenting the therapeutic potency of MSC in treatment of vascular injury promoted by miR-217.